2004
DOI: 10.1016/j.cub.2004.08.059
|View full text |Cite
|
Sign up to set email alerts
|

Visually Induced Plasticity of Auditory Spatial Perception in Macaques

Abstract: When experiencing spatially disparate visual and auditory stimuli, a common percept is that the sound originates from the location of the visual stimulus, an illusion known as the ventriloquism effect. This illusion can persist for tens of minutes, a phenomenon termed the ventriloquism aftereffect. The underlying neuronal mechanisms of this rapidly induced plasticity remain unclear; indeed, it remains untested whether similar multimodal interactions occur in other species. We therefore tested whether macaque m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
52
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 21 publications
11
52
0
Order By: Relevance
“…One modality can dramatically influence the other. Estimates of the location of sound sources are reliably biased in the direction of a task-irrelevant displaced visual cue in humans and in monkeys Knudsen 1985, 1989;Kopco et al 2009;Recanzone 1998Recanzone , 2009Woods and Recanzone 2004). Participants in such ventriloquism experiments are subject to a direct effect of visual information on auditory percepts.…”
Section: Discussionmentioning
confidence: 99%
“…One modality can dramatically influence the other. Estimates of the location of sound sources are reliably biased in the direction of a task-irrelevant displaced visual cue in humans and in monkeys Knudsen 1985, 1989;Kopco et al 2009;Recanzone 1998Recanzone , 2009Woods and Recanzone 2004). Participants in such ventriloquism experiments are subject to a direct effect of visual information on auditory percepts.…”
Section: Discussionmentioning
confidence: 99%
“…Perturbing the visual input during development has been shown to produce compensatory changes in the auditory map of space so as to maintain topographic alignment between the two. More recent studies have shown that, under certain conditions, such effects can also be demonstrated in the mature animal (Brainard and Knudsen 1998;Zwiers et al 2003;Bergan et al 2005;Linkenhoker and Knudsen 2002;Woods and Recanzone 2004) indicating that this influence is not fundamentally restricted to some limited sensitive period of development.…”
Section: Recalibration To Modified Spectral Cuesmentioning
confidence: 99%
“…Spatial ventriloquism not only occurs in humans (e.g., Bertelson and Radeau, 1981), but can also lead to the mislocalisation of auditory cues in rhesus macaques Macaca mulatta (Woods and Recanzone, 2004). Because vocal production mechanisms in vertebrates usually result in the co-occurrence of visual and auditory signals, processing spatial and temporal information can support the receiver's ability to combine the sensory percepts together.…”
Section: Spatio-temporal Correspondencesmentioning
confidence: 99%